Students' experiences in video-recording their real-life conversations / Jenny @ Janey Mosikon, Delia L Olaybal and Bernadette Peter Lidadun (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
This study explores the possibility of utilising students' abilities to video-record their conversations in real-life situations outside the campus. After being taught the conversational skills of asking and giving information, and practising these skills through role-play activities, a group of 27 students was asked to conduct a project, in which they video-recorded their conversations in using the acquired skills in real-life situations such as at Information Technology (IT) and computer shops and other stores selling electrical appliances. The video recordings were analysed and the students were interviewed to explore their experiences in demonstrating the conversational skills of asking and giving information in real-life situations. Data were collected in the form of students' narratives of their experiences before, during and after the project. The findings highlighted how video-recording of students' real-life conversations outside the campus could be used as a learning tool as well as an assessment method for teachers, as the project did not only involve multiple skills in planning, executing and producing, but most importantly it proved to be an observable demonstration of the students' learning after having learnt the skills in the classroom. This paper is expected to aid teachers and syllabus designers in focusing on the facilitation of the desired outcomes.